2016
DOI: 10.1016/j.rchipe.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Validez del Ages & Stages questionnaires para predecir el desempeño cognitivo en los primeros años de educación escolar

Abstract: Introduction: The Ages and Stages questionnaires (ASQ) has been recently validated in our country for developmental screening. The objective of this study is evaluate the validity of ASQ to predict low cognitive performance in the early years of schooling. Patients and method: Diagnostic test studies conducted on a sample of children of medium-high socioeconomic level were evaluated using ASQ at least once at 8, 18 and/or 30 months old, and later, between 6 and 9 years old, reevaluated using the Wechsler Intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
2
7
0
1
Order By: Relevance
“…Findings indicated that the prevalence of cases of children with levels of typical neurodevelopment for their age was 77.3% (n=360), and that the prevalence of a deficit in one or more of the neurodevelopmental areas evaluated by the ASQ-3 was 22.7% (n=106). Similar results were found in Kyerematen et al, 16 Wei et al, 22 Schonhaut et al 28 and Romero-Otalvaro et al 13 Table 1 shows the distribution of the cases with a deficit according to age in the ASQ-3 and EAD-3. Moreover, looking at neurodevelopmental areas evaluated in the ASQ-3, the prevalence analysis revealed that the gross motor skill scale showed the highest deficit distribution (11.8%), followed by the fine motor skill scale (9%).…”
Section: Prevalence Of Neurodevelopment Deficits In Children Of 1 To ...supporting
confidence: 84%
“…Findings indicated that the prevalence of cases of children with levels of typical neurodevelopment for their age was 77.3% (n=360), and that the prevalence of a deficit in one or more of the neurodevelopmental areas evaluated by the ASQ-3 was 22.7% (n=106). Similar results were found in Kyerematen et al, 16 Wei et al, 22 Schonhaut et al 28 and Romero-Otalvaro et al 13 Table 1 shows the distribution of the cases with a deficit according to age in the ASQ-3 and EAD-3. Moreover, looking at neurodevelopmental areas evaluated in the ASQ-3, the prevalence analysis revealed that the gross motor skill scale showed the highest deficit distribution (11.8%), followed by the fine motor skill scale (9%).…”
Section: Prevalence Of Neurodevelopment Deficits In Children Of 1 To ...supporting
confidence: 84%
“…Juneja et al () found the 24‐ and 18‐month ASQs had greater sensitivity than younger age interval questionnaires, demonstrating a trend similar to Gollenberg et al (). In contrast, increased accuracy in detecting developmental delay using the 8‐month ASQ in comparison to older age ASQs was seen by Schonhaut et al (). These inconsistencies bring about the question of the ASQ's sensitivity to control for age variation when screening for developmental delays.…”
Section: Introductionmentioning
confidence: 91%
“…Limbos and Joyce () found that the ASQ‐2 had a consistent and moderate sensitivity and specificity across age groups, using the American Academy of Pediatrics's recommended ages for screening. However, other studies have reported great variation in scores and conflicting sensitivity and predictive value of ASQ scores of different age questionnaire intervals (Group ; Juneja et al ; Janson et al ; Gollenberg et al ; Schonhaut et al ). Janson et al () found that in a sample of 2633 children with ASQ‐2 scores, 10% of children within the appropriate age for a given screening interval received a positive screening in comparison to 22% of children 1–2 months too young and 5% of children 1–2 months too old.…”
Section: Introductionmentioning
confidence: 98%
“…Las experiencias en el hogar son determinantes para el éxito en el aprendizaje, ligadas a la presencia de un entorno familiar estimulante 7,8 . Estudios apoyan que los ambientes enriquecidos culturalmente pueden asociarse a mejores rendimientos en el campo cognitivo y académico 9,10 , estos resultados refuerzan la recomendación sobre el apoyo de la educación infantil en contextos familiares, educativos y la evaluación constante del desarrollo 11 .…”
Section: Introductionunclassified